On finitely g-supplemented modules - Celil Nebiyev; Hasan Hüseyin Ökten (Miskolc Mathematical Notes)
In this work, some properties of finitely g-supplemented modules are investigated. Let MR−NMM∕Nf:M→NRMNMRadgM≤U≤MUU∕RadgMM∕RadgM